Adjunctive effect of 0.2% Chlorhexidine-hyaluronic acid gel in non-surgical treatment of posterior-teeth periodontitis in patients with type 2 diabetes mellitus: A split-mouth study - Cuong, Nguyen Anh; Dung, Tran Van; Thao, Do Thi (Tạp chí Nghiên cứu Y học, 2026)
Periodontitis is more common and often more severe in patients with type 2 diabetes, especially in posterior teeth, where anatomical complexity may hinder plaque control and treatment. This split-mouth controlled clinical trial evaluated the adjunctive effect of locally delivered 0.2% chlorhexidine-hyaluronic acid gel in patients with type 2 diabetes and periodontitis involving posterior teeth. Thirty-three eligible patients were consecutively recruited at the Dental Clinic of Phu Nhuan District General Hospital, Ho Chi Minh City. All participants received non-surgical periodontal therapy on both sides, while the intervention side additionally received subgingival 0.2% chlorhexidine-hyaluronic acid gel at baseline and day 7. Baseline characteristics included a mean age of 64.1 ± 10.5 years old, diabetes duration of 7.3 ± 4.0 years, and HbA1c of 7.2 ± 1.4%. Periodontal status was comparable between sides at baseline. Both groups showed significant improvement in all periodontal parameters at 1 and 3 months. However, the intervention side demonstrated greater short-term improvement, with lower periodontal pocket count, better clinical periodontal parameters, and a more marked reduction in periodontitis severity. Adjunctive local 0.2% chlorhexidine-hyaluronic acid gel enhanced the short-term effectiveness of non-surgical periodontal therapy in this high-risk population.